'Being the bridge and the beacon': a qualitative study of the characteristics and functions of the liaison role in child and family health services in Australia. Issue 1 (19th September 2016) - Olley, Hannah; Psaila, Kim; Fowler, Cathrine; Kruske, Sue; Homer, Caroline; Schmied, Virginia
Abstract : Aims and objectives: This article explores the characteristics and functions of the liaison role in child and family health services in Australia. Background: Liaison roles are increasingly being used to improve communication between health services and professionals and to facilitate access to support for individuals and families in need. Nurses are commonly, although not always, the professionals who undertake these roles. Research on the role and outcomes of liaison positions in child and family health services is limited in Australia and internationally. Design: A qualitative interpretive design informed this study. Interviews and focus groups were conducted with 40 liaison and other health professionals, primarily nurses, working with families with newborn and young children in two Australian States. Data were analysed thematically. Results: Three major themes were identified reflecting the importance of defining the role and tasks which included building bridges between services and professionals, supporting families during transition between services and supporting clinicians. Several facilitators and barriers were identified, including concerns about sustainability of the roles. Conclusions: Professionals working in a liaison role in child and family health services emphasise that these positions have the potential to link services and professionals, thereby providing more effective care pathways for children and families especially for those with complex and multiple vulnerabilities. While a few children and family health services in Australia provide liaison services, the extent of liaison support and the outcomes for families in Australia is unknown. Relevance to clinical practice: Nurses working with children and families are the most likely health professionals to undertake a liaison role. In many nursing contexts, liaison roles are relatively new and those in the role have the responsibility to define the key purpose of their role. Liaison roles are multifaceted requiring the nurse to have excellent communication and negotiation skills to effectively link diverse professionals and services, while simultaneously engaging with and supporting vulnerable families and children. Nurses in these roles also support and educate clinical colleagues.